Brexit and the EU–UK free trade agreement: dos and don'ts when drafting rules of origin. Issue 2 (17th June 2019) - Soprano, Roberto
Abstract : Purpose: The purpose of this paper is to highlight the pros and cons of different models of the European Union (EU)-style Rules of Origin (RoO) that could be chosen by negotiators for a future UK–EU Free Trade Agreement (FTA). It will also underline the impact that any choice would have on economic operators and certain criteria that should be evaluated before taking any decisions on the adoption of RoO. Design/methodology/approach: The paper will describe three different RoO models that could be chosen by negotiators. For each of them, it analyses the pros and cons and the impact on economic operators. Findings: The choice of a RoO would have an impact on future EU–UK trade relations. It will affect the utilization rate of the FTA as well as investment (and divestment) corporate strategies in the UK and EU. Originality/value: The paper introduces different criteria to evaluate the impact of RoO that should be taken into consideration by negotiators. It emphasizes that RoO should be simple, predictable, coherent, IT compatible and easily adaptable.